2020
DOI: 10.5114/aoms.2020.100401
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among cancer patients qualified for systemic treatment. Analysis of a cardiovascular disease-free cohort from the Polish multicentre study ONCOECHO

Abstract: Introduction: Cancer therapies are currently more efficient at increasing the survival of patients (pts) with cancer. Unfortunately, the cardiovascular (CV) complications of cancer therapies may adversely affect improving results of treatment. The aim of the study was to evaluate the prevalence of classical CV risk factors among pts with de novo diagnosis of cancer and thus identify the cohort of pts with potentially increased future risk of CV complications. Material and methods: The analysis is based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…The compared groups of hematological patients receiving cardiology consultations proved to be quite homogeneous. We observed slightly fewer risk factors for cardiovascular events as compared to those reported in the literature, which may be due to the relatively younger age of the studied patients [ 22 , 23 ]. In the 651 consulted patients, cardiac complications due to hemato-oncological therapy were identified in 57 patients, of which most were mild.…”
Section: Discussioncontrasting
confidence: 67%
“…The compared groups of hematological patients receiving cardiology consultations proved to be quite homogeneous. We observed slightly fewer risk factors for cardiovascular events as compared to those reported in the literature, which may be due to the relatively younger age of the studied patients [ 22 , 23 ]. In the 651 consulted patients, cardiac complications due to hemato-oncological therapy were identified in 57 patients, of which most were mild.…”
Section: Discussioncontrasting
confidence: 67%
“…In a Polish study, it was found that cancer patients were more likely to be smokers, hypertensives, and diabetics than the general population. 34 In this cohort study, 743 CRC patients had hypertension history. In the multivariable regression analysis, CRC patients with prior hypertension history had 1.6 times higher risk of cardiotoxicity than nonhypertensives, a finding that was similar to that found in a previous study.…”
Section: Discussionmentioning
confidence: 96%
“…There has been an association between pre‐existent CV disease and an increased risk of cardiotoxicity in patients treated with chemotherapy 24 . Cancer patients may also have an increased prevalence of significant CV risk factors indicating the need for closer cardiac monitoring during their anti‐cancer treatment 25 . However, the relationship between traditional CV risk factors and ICI use on the subsequent development of CVT could not be comprehensively assessed from our cohort due to the lack of reporting of CV risk factors.…”
Section: Discussionmentioning
confidence: 99%